2005
DOI: 10.1124/jpet.105.092825
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Antinociceptive Effect of the Flavonoid Myricitrin: Evidence for a Role of the l-Arginine-Nitric Oxide and Protein Kinase C Pathways

Abstract: The present study investigated the antinociceptive effects of the flavonoid myricitrin in chemical behavioral models of pain in mice and rats. Myricitrin given by i.p. or p.o. routes produced dose-related antinociception when assessed on acetic acidinduced visceral pain in mice. In addition, the i.p. administration of myricitrin exhibited significant inhibition of the neurogenic pain induced by intraplantar (i.pl.) injection of capsaicin. Likewise, myricitrin given by i.p. route reduced the nociception produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(87 citation statements)
references
References 38 publications
4
75
0
6
Order By: Relevance
“…Recent studies report antidepressive, antineoplastic, antitumor and antiviral activities of hypericin [18]. Flavonoids contribute to the anti-inflammatory effects of the plant [32] and antinociceptive properties have been reported for the flavonoid myricitrin [33]. Enzyme assays performed on rat brains demonstrated that hypericin and pseudohypericin are potent and selective inhibitors of the protein kinase C (PKC) [34,18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report antidepressive, antineoplastic, antitumor and antiviral activities of hypericin [18]. Flavonoids contribute to the anti-inflammatory effects of the plant [32] and antinociceptive properties have been reported for the flavonoid myricitrin [33]. Enzyme assays performed on rat brains demonstrated that hypericin and pseudohypericin are potent and selective inhibitors of the protein kinase C (PKC) [34,18].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports [16], our results showed that myricitrin increased HO-1 and NQO-1 expression, activated Akt phosphorylation and promoted Nrf2 signaling. Recent researches have reported that myricitrin can effectively inhibit protein kinase C pathways, which are mostly focus on antipsychotic effects of the agent [37,38]. It is highly limited to search for the related literature on myricitrin, as a PKC inhibitor to fight against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, information regarding the effect of arginine on PKC signalling in fish is lacking. Work in mice showed that dietary arginine activated PKC in paw tissue [26]. These findings indicated that a likely correlation exists between arginine and PKC signalling molecules involved in TJ mRNA expression in fish intestine, which requires additional exploration.…”
Section: Introductionmentioning
confidence: 95%